Transcriptional and Metabolomic Analysis of L-Arginine/Nitric Oxide Pathway in Inflammatory Bowel Disease and Its Association with Local Inflammatory and Angiogenic Response: Preliminary Findings - Krzystek-Korpacka, Małgorzata (Int J Mol Sci, 2020)
L-arginine/nitric oxide pathway in Crohn’s disease (CD) and ulcerative colitis (UC) is poorly investigated. The aim of current study is to quantify pathway serum metabolites in 52 CD (40 active), 48 UC (33 active), and 18 irritable bowel syndrome patients and 40 controls using mass spectrometry and at determining mRNA expression of pathway-associated enzymes in 91 bowel samples. Arginine and symmetric dimethylarginine decreased (p < 0.05) in active-CD (129 and 0.437 µM) compared to controls (157 and 0.494 µM) and active-UC (164 and 0.52 µM). Citrulline and dimethylamine increased (p < 0.05) in active-CD (68.7 and 70.9 µM) and active-UC (65.9 and 73.9 µM) compared to controls (42.7 and 50.4 µM). Compared to normal, CD-inflamed small bowel had downregulated (p < 0.05) arginase-2 by 2.4-fold and upregulated dimethylarginine dimethylaminohydrolase (DDAH)-2 (1.5-fold) and arginine N-methyltransferase (PRMT)-2 (1.6-fold). Quiescent-CD small bowel had upregulated (p < 0.05) arginase-2 (1.8-fold), DDAH1 (2.9-fold), DDAH2 (1.5-fold), PRMT1 (1.5-fold), PRMT2 (1.7-fold), and PRMT5 (1.4-fold). Pathway enzymes were upregulated in CD-inflamed/quiescent and UC-inflamed colon as compared to normal. Compared to inflamed, quiescent CD-colon had upregulated DDAH1 (5.7-fold) and ornithine decarboxylase (1.6-fold). Concluding, the pathway is deregulated in CD and UC, also in quiescent bowel, reflecting inflammation severity and angiogenic potential. Functional analysis of PRMTs and DDAHs as potential targets for therapy is warranted.